Foundational principles of contract law - Eisenberg, Melvin Aron (New York, NY : Oxford University Press, 2018)
'Foundational Principles of Contract Law' is a one-volume treatise on a given legal subject that is intended primarily for law-school students.
Previously issued in print: 2018.
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from home page (viewed on September 20, 2018).
Keywords: Contracts -- United States; Contracts; Law; Laws of specific jurisdictions & specific areas of law